Intracellular Acinetobacter baumannii acts as a transient reservoir in lung infection via a “persist and resist” strategy - Manon Janet-Maitre; Gisela Di Venanzio; Clay D. Jackson-Litteken; Nichollas E. Scott; Mario F. Feldman (Proceedings of the National Academy of Sciences, 2025)
Although considered primarily extracellular, Acinetobacter baumannii can survive and replicate within macrophages in vitro. Intracellular bacteria are often protected from the host immune system and antibiotic treatment, potentially leading to chronic or recurrent infections. To investigate the role of intracellular A. baumannii during infection, we transferred b roncho a lveolar l avage f luid (BALF) from infected mice, containing an intracellular bacterial population, into naïve immunocompromised mice, enabling us to assess the fate of bacteria following internalization. The BALF transfer resulted in A. baumannii lung infection, indicating that intracellular bacteria can egress from host immune cells and establish infection in the lungs, thereby acting as a transient reservoir during pulmonary infection. Using dual proteomics, we characterized the A. baumannii –macrophage interactions. Infected macrophages exhibit an inflammatory and type I interferon response, marked by increased Acod1/IRG1 protein levels. Intracellular A. baumannii upregulates proteins involved in evading nutritional immunity, stress response, surface modification, and metabolic adaptation. Collectively, these findings indicate that A. baumannii employs a multifactorial strategy to persist and replicate within macrophages, potentially shaping infection dynamics in vivo and undermining therapeutic efficacy.